Understanding gas-phase breakout with high H2 content in CCS pipeline gathering networks. (November 2019) - Healey, Matthew; Mistry, Ketan; Jones, Thomas; Luna-Ortiz, Eduardo
Highlights: H2 is a potential contaminant of CO2 streams in pre-combustion capture or hydrogen production. There is a risk for long-term exposure of H2 -rich gas breakout to certain parts of a CCS gathering and injection network. A concentration as high of 20% mol (bubble point) can be reached at certain conditions. New and repurposed facilities for CO2 transportation shall consider high local hydrogen concentration. H2 in CO2 streams has the greatest impact in the physical properties. Thermodynamic modelling is very challenging. Abstract: An accurate understanding of the behaviour of impure carbon dioxide (CO2 ) during pipeline transport stage is required for commercial scale deployment of Carbon Capture and Storage (CCS) networks. Impurities in the CO2 stream modify phase behaviour and change the thermophysical and transport properties of the stream. CO2 streams containing hydrogen (H2 ) are a particular challenge due to the unique physical properties of H2 . In a CCS gathering network where CO2 is sourced from processes such as pre-combustion capture or hydrogen production, H2 with a concentration of 2% mol can be expected to be present in the mixture. This paper describes foreseeable operating scenarios where gas breakout in single-phase CCS gathering networks might occur, leading to pockets of gas with high H2 concentration. Multiphase flow modelling of a CCS gathering network with impure CO2 containing H2 has been performed, demonstrating these operating scenarios and providing a basis for design. The H2 content of the gas breakout is shown to be >20% mol when the conditions are close to bubble point. High concentrations of H2 due to gas breakout must be considered as part of a single-phase CCS gathering network design, whenever H2 is present. This paper provides practical guidelines for understanding, quantifying and, managing the worst design cases for H2 exposure due to gas breakout. Specific recommendations for what must be included in the project design basis are presented. Potential mitigating factors and engineering measures that can be taken to manage high H2 concentration in a CCS system are also discussed.